HUBUNGAN LOCUS OF CONTROL DENGAN KOMITMEN ORGANISASI PERAWAT DI RUANG RAWAT INAP RUMAH SAKIT - Rachmawati Rachim; Abd. Rahman Kadir; Werna Nontji (Politeknik Kesehatan Kemenkes Mamuju, 2016)
Nurses’ organizational commitment can be affected by characteristics of individuals and organizations locus of control is one domain of personality. This study aimed to analyze the relationship between locus of control with organizational commitment. This research was an analytic survey with cross-sectional study. The samples were implementer nurses in inpatient rooms as many as 63 people selected using total sampling method. The data were obtained using questionnaires by respondents. Chi-square test was used to test the relationship of locus of control with nurse organizational commitment. The results of the research indicate that there is a significant relationship between locus of control with organizational commitment nurses (p = 0.003). Advised to consider the type of locus of control in placing nurses, especially afectif commitment and normative, and further research on organizational variables to strengthen the study.